The Role of Spiritual Leadership in Enhancing Quality of Work Life, Job Satisfaction, and Organizational Commitment among Lecturers at Islamic Private Universities - Ilham, Ilham; Sukmawati, St.; Olle, Andi Tenri; Lahadji, Murad (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2025)
This study examines the moderating role of spiritual leadership in the relationship between quality of work life, job satisfaction, and organizational commitment among lecturers at Islamic private universities in Indonesia. A quantitative cross-sectional design was employed using survey data collected from 323 permanent lecturers. Data were analyzed using partial least squares structural equation modeling (PLS-SEM). The findings indicate that quality of work life and spiritual leadership significantly influence organizational commitment among lecturer at Islamic private universities in Indonesia. Moreover, spiritual leadership strengthens the relationships between quality of work life and organizational commitment as well as between job satisfaction and organizational commitment, although spiritual leadership does not directly affect organizational commitment. These results suggest that spiritual leadership enhances organizational commitment indirectly by reinforcing supportive work conditions and positive job-related attitudes. This study contributes to the literature on spiritual leadership by clarifying its contextual role in higher education institutions with strong spiritual and ethical values.